Nielsen - Elias, Jaan; Dhar, Ravi; Iwata, Jon; Sudhir, K.; Kraus, Michael W.; Dupree, Cydney H.; Taub, Melanie (London : Yale School of Management, 2022)
Nielsen has been measuring audiences since radio was the primary form of mass communication, and the company's data on the popularity of particular programs (ratings) have become the industry's standard. For more than 80 years, Nielsen ratings have determined the amount advertisers pay for hawking their wares during programs, determining which programs prosper and which are canceled. To be sure, the company has been criticized, generally by those entities whose programs lag in popularity and believe that "their" audience is not being determined properly. However, the company's measurements remain the primary instrument for describing viewership; so much so that the entertainment and advertising industries refer to Nielsen ratings as "currency."The events of 2020-21, however, challenged Nielsen's audience measurement business as it had never been challenged before. The Covid pandemic meant that Nielsen's field force could no longer visit the homes of current and prospective panelists. Machines were not serviced, and the panel could not be refreshed according to plan. Nielsen itself acknowledged that the ratings it was reporting might no longer be representative of the actual audience. Though major advertisers and networks continued to use Nielsen numbers to set ad rates, the Media Rating Council (MRC), a body constituted by the government to oversee ratings, suspended Nielsen's accreditation for the first time since its founding. Nielsen must now adapt and change methodology to regain accreditation and stable profit.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nielsen Media Research; Strategic planning -- Case studies; Business planning -- Case studies; Organizational change -- Case studies; Customer relations -- Management -- Case studies